Studi Al-Qur'an Sebagai Pemicu-Pemacu Peradaban: Telaah Sosio-Historis - Muhammad Taufik (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Various studies have been expressed about the progress of Islamic civilization which is strongly influenced by contact with outside traditions, both Greek, Persian, Indian, and so forth. But the important thing that also needs to be underlined is that Islam itself has the values and teachings of the Qur'an which is the main driver of the birth of Islamic civilization. The Qur'an has a very vital and respected position in Muslim communities throughout the world. Aside from being a source of law, moral guidance, guidance of worship and doctrine of the faith, the Qur'an is also a historical and universal source of civilization. This paper will further explore how the embodiment of Islam as a civilization and the historicity of the Qur'an as a trigger for civilization